PENGEMBANGAN MODEL MATERI AJAR SINTAKSIS BERBASIS LINGUISTIK FUNGSIONAL DI JURUSAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS NEGERI JAKARTA - Miftahul A., Khairah (2012)
This study is based on the reality that most of the instructional materials used in the course of syntax is based on formalist or structuralist paradigm, which is emphasized on the structural aspects and less attention on the aspects of meaning and context. Because the priority of sturcturalist and formalist syntax is the correctness of the structure, so the examples of sentences as it is presented in the instructional materials of syntax are not varied as it is used in real communication situations. The presence of this material is certainly not conducive to the achievement of the expected course of syntax. Therefore, this study aims to develop a model of teaching materials of syntax based on functional linguistics which is suitable to student at Indonesia Language and Literature Study Program of State University of Jakarta. According to functionalist paradigm, the unit of language cannot be separated from its function in daily or real using because the function that determine the structure. Study of the structure cannot be separated from meaning and context. Functional paradigm developed in this study was adapted from the concept of functional linguistics of Valin, Simon Dik, Halliday, and Harimurti. The method used to develop the instructional material for this study is the method of research and development model that of Borg and Gall which included the stages: preliminary stage, the model development stage, and the evaluation stage. Activities undertaken at the preliminary stage is documentation study and analysis need. Activity that performed on the phase of development model is drawing up the syllabus and teaching materials in order to develop a model of instructional material of syntax based on functional linguistics. Activity undertaken in evaluating phase is the expert testing, first testing (limited), second testing, and field testing. This research led to the findings, namely (1) assume that functional linguistic can be applied to the learning of syntax, (2) form phrases, clauses, and sentences are very varied, (3) first testing, second testing, and field testing indicate that there is a significant difference between the average value of the pretest and postest achieved by students in each unit tested. Thus, the teaching materials of syntax based on functional linguistics is feasible and effective in improving student competence of syntactic at Indonesian Language and Literature Study Program of the State University of Jakarta.